(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to demonstrate the reflection of the audit of modern irrigation technologies according to the updated International Standard for Related Services (4400) on the external auditor’s report in line with the new trends regarding the adoption of international standards in the Iraqi environment. The research problem focused on the lack of comprehensiveness of audit programs that address the audit of modern irrigation technologies according to assurance engagements to contribute to obtaining governing evidence. The research was based on a hypothesis that the audit of modern irrigation technologies according to the updated International Standard for Related Services (4400) affects the external auditor’s report. To achieve the research objectives, the descriptive analytical approach was adopted in the practical aspect by studying and analyzing the data and information obtained from the parties related to the research topic with the aim of reaching objective conclusions based on realistic practical facts. The project of using modern irrigation technologies affiliated with the Ministry of Agriculture and the General Company for Agricultural Equipment was taken as a field of application. One of the most important conclusions reached by the researchers was that the absence of technical and specialized coverage of the audit reports had an impact on providing a complete and accurate picture of the work of the project of using Modern irrigation technologies and what prevents the benefit of specialized auditing techniques that can help improve and develop the project based on the discovered facts provided by the reports, which are provided by these reports based on the relevant international standards, specifically the updated standard (4400) to make informed decisions or to correct the course if necessary. The most important recommendations were that adopting the proposed report guide based on the updated international standard for related services (4400) results in reports that reflect the actual reality of the project’s work, as the discovered facts provided by these reports help their users to draw their own conclusions and make decisions that contribute to correcting the course and improving the project’s work and developing it.